MicroRNA-296: a promising target in the pathogenesis of atherosclerosis? - Heng Li; Xin-Ping Ouyang; Ting Jiang; Xi-Long Zheng; Ping-Ping He; Guo-Jun Zhao (BMC, 2018)
Abstract Atherosclerosis has been recognized as an inflammatory disease involving the vascular wall. MicroRNAs are a group of small noncoding RNAs to regulate gene expression at the transcriptional level through mRNA degradation or translation repression. Recent studies suggest that miR-296 may play crucial roles in the regulation of angiogenesis, inflammatory response, cholesterol metabolism, hypertension, cellular proliferation and apoptosis. In this review, we primarily discussed the molecular targets of miR-296 involved in the development of atherosclerosis, which may provide a basis for future investigation and a better understanding of the biological functions of miR-296 in atherosclerosis.